2022
DOI: 10.31756/jrsmte.523
|View full text |Cite
|
Sign up to set email alerts
|

­The Scientific Approach of The Indonesian 2013 Curriculum: A Comparison with OtherActive Learning Strategies in Mathematics

Abstract: The Indonesian 2013 curriculum is an improvement on the previous curriculum, namely the Education Unit Level Curriculum (KTSP). The implementation of the 2013 curriculum strongly emphasizes a Scientific Approach with student-centred learning to prepare Indonesian citizens to have the ability to live as individuals and citizens who are productive, creative, and innovative. The Scientific Approach is a learning process designed so that students actively construct concepts and principles through the stages of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The classes were conducted both offline and online, so Androidbased learning media can be used in this school. This is in agreement with research conducted by Kartini & Setiawan (2019), who found that the media is following the K-13's student-centred method, in which students are active and learn independently (Muhammad et al, 2022). The results of the interview also informed that public secondary schools, particularly in Semarang, use textbooks and worksheets.…”
Section: Resultssupporting
confidence: 90%
“…The classes were conducted both offline and online, so Androidbased learning media can be used in this school. This is in agreement with research conducted by Kartini & Setiawan (2019), who found that the media is following the K-13's student-centred method, in which students are active and learn independently (Muhammad et al, 2022). The results of the interview also informed that public secondary schools, particularly in Semarang, use textbooks and worksheets.…”
Section: Resultssupporting
confidence: 90%
“…Collaborative learning practices such as the scientific approach and learning models have been widely tested for effectiveness in several empirical studies (Muhammad et al, 2022). Jazuli et al, (2017) emphasized that learning will be meaningful if it relates the students' real-life experiences to mathematical ideas or concepts in the learning process in the classroom through contextual problems.…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…For example, our May edition included a very noteworthy article by Rosida Rakhmawati Muhammad and colleagues from Coventry University in the United Kingdom. Their study used a theoretical approach to investigate the Indonesian science curriculum resulting in a set of recommendations to improve teacher training in Indonesia (Muhammad et al, 2022. ) The article has already been cited in two other peer-reviewed articles.…”
mentioning
confidence: 99%